2022
DOI: 10.1017/ice.2021.517
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis attributed to transmission within healthcare facilities, Botswana—The Kopanyo Study

Abstract: Objective: Healthcare facilities are a well-known high-risk environment for transmission of M. tuberculosis, the etiologic agent of tuberculosis (TB) disease. However, the link between M. tuberculosis transmission in healthcare facilities and its role in the general TB epidemic is unknown. We estimated the proportion of overall TB transmission in the general population attributable to healthcare facilities. Methods: We combined data from a prospective, population-based molecular epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Nosocomial transmission of MTBC infection in high-burden settings has been reported previously ( 5 7 ). We prospectively aimed to detect transmission events of MDR/RR strains of MTBC at the TB referral center in Moldova, a country of high MDR/RR TB incidence.…”
Section: Discussionmentioning
confidence: 65%
“…Nosocomial transmission of MTBC infection in high-burden settings has been reported previously ( 5 7 ). We prospectively aimed to detect transmission events of MDR/RR strains of MTBC at the TB referral center in Moldova, a country of high MDR/RR TB incidence.…”
Section: Discussionmentioning
confidence: 65%
“… 5 A recently published molecular epidemiological study from Botswana concluded, similarly, that 3–8% of Mtb transmission resulting in TB disease might be attributable to contact in healthcare facilities. 6 …”
Section: Tb-ipc Is Highly Cost-effective and Needs Investmentmentioning
confidence: 99%
“…5 A recently published molecular epidemiological study from Botswana concluded, similarly, that 3-8% of Mtb transmission resulting in TB disease might be attributable to contact in healthcare facilities. 6 Cost-effectiveness analyses suggest that all of the TB-IPC interventions modeled, including combinations of these interventions, are highly cost-effective. 54 We used the current opportunity cost-based threshold for South Africa, estimated at US$3,200 per disability-adjusted life-year (DALY) averted.…”
Section: Implementation Will Not Improve Unless Upstream Facility-lev...mentioning
confidence: 99%
See 2 more Smart Citations